THE DISCOVERY LEARNING MODEL INFLUENCE ON STUDENT CRITICAL THINKING ABILITIES AND CHEMISTRY LEARNING OUTCOMES IN MA. MU'ALLIMAT NWDI PANCOR - Laili, Putri Ispani Maulidayatul; Raehanah; Multazam (UIN Mataram, 2023)
This study aims to determine the effect of the discovery learning model on critical thinking skills and student chemistry learning outcomes at MA Mu'allimat NWDI Pancor in multivariate and univariate ways. The type of research used is a quasi-experimental research design with a post-test only control group design. The sampling technique in this study was cluster random sampling. The research samples were class XI IPA 2 as the experimental class with 34 students and class XI IPA 1 as the control class with 34 students. The instrument used to measure critical thinking skills is a description test of 5 questions and learning outcomes of 16 multiple choice questions. Based on the results of the study it can be concluded that: a) There is an influence of the discovery learning model on students' critical thinking skills at MA Mu'allimat NWDI Pancor, as evidenced by the sig value of 0,007 <0,05. b) There is an influence of the discovery learning model on students' chemistry learning outcomes at MA Mu'allimat NWDI Pancor, as evidenced by the sig value of 0,001 <0,05. c) There is an influence of the discovery learning model on critical thinking skills and students' chemistry learning outcomes at MA Mu'allimat NWDI Pancor in a multivariate manner as evidenced by a sig value of 0,000 <0,05.